Preservação digital na gestão da informação: um modelo processual para as instituições de ensino superior - Grácio, José Carlos Abbud [UNESP] (2011)
Society has witnessed a cultural change in the use of information due to new technologies, mainly to computers and Internet. In this context, preservation of digital information emerges as a great challenge to be faced by information professionals, mainly derived from the constant enhancements and changes in information and communication technology (ICT), and in the environments in which information is inserted. Along with this new challenge, a new research area has been initiated, that of digital preservation whose agenda includes problems such as obsolescence of technological equipment (hardware), of computer programs (software), of information supports and of storage formats. Besides technological problems, digital preservation involves cultural, legal and managerial aspects. Although the concerns of the Information Area on the theme have been increasing, there is a need in literature to offer a sound theoretical discussion on issues related to it, and this is the proposal which may turn this research relevant. From the infinite universe of digital preservation applicability, the environment chosen for this research was that of Higher Education Institutions (HEI), where there has been an explosion of documents in digital form produced by teaching-learning activities in graduation and post graduation programs, research projects and community services. The aim of this investigation is to propose a processual management model for digital information preservation in HEI, by means of sound theoretical research on all the aspects involved in the preservation process and on the main information management models. The model should account for any type of HEI, any type of digital document, any type of academic information, and organizational culture should guide all processes. To achieve this goal, the exploratory methodology is adopted in order to be able to obtain a full understanding... (Complete abstract click electronic access below)